MiR-4298 and lncKRTAP5-6-3 regulated Cathepsin D expression through ERK-MAPK signaling pathway in chronic UVB-damaged HaCaT cells - Chen, Xinling; Zhou, Feng; Lin, Yao; Xia, Yue; Zhang, Jie; Hou, Wenyi; Sun, Yu; Lai, Wei; Zheng, Yue (Frontiers in Medicine, 2025)
ObjectiveMiRNAs and lncRNAs are important regulators in the process of skin photoaging. In this study, we investigated the expression changes and interactions between miR4298 and lncKRTAP5-6-3 in chronically UVB-damaged human keratinocyte cell line (HaCaT) cells and explored miR4298-MAPK/ERK signaling pathway-Cathepsin D-lncKRTAP5-6-3 mechanisms in photoaging cells.MethodsHaCaT cells were irradiated with 12 mJ/cm2 UVB once a day for 7 days. miR-4298 mimics and miR-4298 inhibitors were transfected into HaCaT cells by lipo3000 transfection reagent, and the HaCaT cells were divided into three groups: blank control group; UVB-damaged group; and UVB damage+miR-4298 regulation (overexpression or inhibition) group. The expression levels of miR4298 and lncKRTAP5-6-3 were quantitatively analyzed using RT-PCR, while the expression of Cathepsin D and MAPK/ERK signaling pathway proteins was detected using Western blot.ResultsAfter 7 consecutive days of UVB irradiation, the expression of miR-4298 decreased by 0.64 ± 0.06 (P < 0.001) compared to the un-irradiated HaCaT cells, and the expression of the KRTAP5-6-3 decreased by 0.80 ± 0.13 (P < 0.001) compared to the control group. The expression of p-ERK signaling was increased by 0.9437 ± 0.1186 (P < 0.0001), and Cathepsin D was decreased by 0.6163 ± 0.075 (P < 0.0001). In HaCaT cells transfected with miR-4298 mimics and then irradiated by UVB for 7 days, the expression of lncKRTAP5-6-3 was increased to 0.5114 ± 0.1438 (P < 0.05)-fold, and the phosphorylation level of ERK signaling was decreased by 0.3880 ± 0.1185 (P < 0.01), while Cathepsin D expression was increased by 0.2617 ± 0.0749 (P < 0.0001) compared to the UVB-damaged group. In HaCaT cells transfected with miR-4298 inhibitors and then irradiated by UVB for 7 days, lncKRTAP5-6-3 was decreased by 0.1697 ± 0.1383, the phosphorylation level of ERK signaling was increased by 1.096 ± 0.7836 (P < 0.05), while Cathepsin D expression was decreased by 0.05197 ± 0.24827 compared to the UVB-damaged group.ConclusionThe synergistic effects of miR4298 and lncKRTAP5-6-3 play important roles in chronic UVB-damaged HaCaT cells by regulating the MAPK/ERK signaling pathway and Cathepsin D expression. This study presents novel targets for intervening in chronic ultraviolet damage (photoaging) skin and UV-related dermatoses.